Research and Application of Cathodic Protection Technology for Underground Pipelines: A Case Study of the IPP Sumsel-5 Water Intake Project - Wang Zhiliang (Journal Of Social Science (JoSS), 2025)
Underground pipelines are exposed to continuous electrochemical corrosion during long-term service, which may result in reduced wall thickness, perforation, and leakage, posing serious risks to operational safety. This study examines the application of cathodic protection (CP) technology as an effective and economically viable corrosion prevention strategy, focusing on the underground water intake pipelines of the Sumsel-5 Independent Power Producer (IPP) project. The objective of this research is to evaluate the effectiveness of a constant-potential CP system in controlling corrosion and maintaining pipeline integrity under real operational conditions. The study employed a case study approach, beginning with on-site assessments of environmental characteristics, corrosion patterns, and baseline electrochemical potential. Subsequent stages included CP system design, installation, and monitoring, with technical parameters tailored to site-specific requirements. Field measurements were conducted to evaluate performance, and maintenance procedures were documented to ensure long-term system stability. The results reveal that the implementation of the constant-potential CP system successfully maintained pipeline surface potential below –0.85 V relative to a saturated calomel electrode, meeting international protection standards. The system demonstrated consistent performance with significant reduction in corrosion risk and enhanced operational reliability. This study provides an applicable technical reference for similar water intake and underground transmission pipeline projects, highlighting the importance of integrated system design, monitoring, and maintenance in achieving sustainable corrosion protection.